Petrophysical Analysis of E5 sand group of Sokor Formation, Termit Basin, Niger - Nasaruddin, M.N. (Institute of Physics Publishing, 2017)
The main objective of well logging is to estimate the petrophysical properties of reservoirs which includes porosity and hydrocarbon saturation for hydrocarbon exploration and production purposes. This paper portrays the result of a wireline log study on the E5 sand group of Sokor Formation of the Paleogene in Termit Basin. The objectives of this research are to differentiate the log characteristics of the sediment in the Sokor Formation and provide a preliminary result of the porosity, permeability and hydrocarbon saturation of the study area. A total number of 3 wells were fully evaluated for this research. A compilation of wirelines data sets availability which includes calliper log, gamma ray log (GR), neutron log (NPHI), density log (RHOB) and resistivity logs (RD and RS) were carefully analysed during this study. Petrophysical analysis reveals that the E5 sand group of Sokor Formation has a very high porosity of up to 28.7 and high hydrocarbon saturation up to 88.7. The suggests future work should include the integration of well log analysis with core analysis. © Published under licence by IOP Publishing Ltd.